Adoption of digital marketing tools in independent businesses: experiences of restaurant entrepreneurs in India and United Kingdom. (31st May 2021) - Dabas, Swati; Sharma, Savita; Manaktola, Kamal
Abstract : Purpose: This paper aims to explore the experience of adoption of digital marketing and related tools by restaurant entrepreneurs or owners of restaurants in the UK and India. Design/methodology/approach: This study is based on qualitative research. In-depth interviews were conducted with restaurant owners to understand the extent of adoption of digital marketing tools and how they have embraced the digital change in running their business operations. Findings: Findings shed light on major changes in consumer behaviour and the readiness of restaurant owners to adopt digital tools for marketing restaurant businesses. Additionally, this paper also probes restaurant owners' apprehensions in the process with an objective of retaining customers for a longer period. Originality/value: It is also evident that there is a clear gap in the restaurant space in India and the UK as far as the adoption of digital marketing tools is concerned. The restaurants in India are yet to adequately harness the digital medium as a strategic tool for marketing. This research can potentially form the basis of further research in terms of using technology and digital tools to reach customers and creating a more personalized experience for them.